(3GdSMQ GdeHjf haJhQ CdMGX GdYjfs - (3eMSf Hf GdMSf Hf GdbGSe GdUfYGfj GdjeGfj,J (B1170 (3g` s ((3UfYGA s)
(3ChdgG (B:s
(3fMeOc Gddge GdTOjO GdeMGd , ebdH GdOgQ MGdkG HYO MGd , aGdCjGe SLGd , hGdLjGO GdCYeGQ HGdQcV ajgG eMGd s
(3BNQgG (B:s
(3hgj WhjdI LjOg Edi ZGjI , hai EKHGJ gPi GdbOQ efgG caGjI hEdi YGe GdKdGjf GfJgi GdLRA GdChd ef GdSMQ GdeHjf s
(3GdfSNI HgG MhGTs
(3Ydi MhGTjgG JYdjbGJ s
(3hgh ai CNHGQ Gdjef hCgdg ef SfI (B1092 - 1150s
(3GdLRA GdChd ef SfI (B1092 -1130 s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
Keywords: (3GdJGQjNs